Dendrobium officinale Prevents Early Complications in Streptozotocin-Induced Diabetic Rats - Hou, Shao-zhen (Evid Based Complement Alternat Med, 2016)
Background. Dendrobium officinale (DO) Kimura et Migo is a precious Chinese herb that is considered beneficial for health due to its antioxidant and antidiabetes properties, and so on. In this research, we try to determine the preventive effect of DO on the early complications of STZ-induced diabetic rats. Methods. Type 1 diabetic rats were produced with a single intraperitoneal injection of STZ (50 mg/kg). DO (1 g/kg/day) was then orally administered for 5 weeks. Blood glucose, TC, TG, BUN, CREA, and GSH-PX levels were determined, and electroretinographic activity and hypoalgesia were investigated. Pathological sections of the eyes, hearts, aortas, kidneys, and livers were analyzed. Results. Treatment with DO significantly attenuated the serum levels of TC, TG, BUN, and CREA, markedly increased the amplitudes of ERG a- and b-waves and Ops, and reduced the hypoalgesia and histopathological changes of vital organs induced by hyperglycemia. The protective effect of DO in diabetic rats may be associated with its antioxidant activity, as evidenced by the marked increase in the serum level of glutathione peroxidase. However, DO had no significant effect on blood glucose levels and bodyweight of diabetic rats. Conclusions. DO supplementation is an effective treatment to prevent STZ-induced diabetic complications.